Assessment of exposure to cobalt and its compounds in Italian industrial settings: Occupational exposure to cobalt - Scarselli, Alberto; Di Marzio, Davide; Iavicoli, Sergio (La Medicina del Lavoro, 2020)
Background: Adverse health effects of occupational exposure to cobalt and its compounds are well-documented. Objectives: The aim of the study is to evaluate exposures to cobalt in Italian industrial settings. Methods: Data on cobalt and its compounds were collected from an occupational exposure registry. Statistical analysis was carried out for some exposure-related variables (i.e., cobalt compound, activity sector, occupational group, firm size). The number of workers potentially exposed was estimated for selected industrial sectors. Results: Overall 1,701 measurements were analyzed in the period 1996-2016. The geometric mean of cobalt airborne concentration was 0.33 µg/m3. Most exposures occurred in the manufacture of fabricated metal products (50%) and among metal finishing-, plating- and coating-machine operators (42%). A total of 30,401 workers potentially exposed to cobalt was estimated, over 72% were male. Conclusions: Identifying professional groups at high-risk of exposure can help to control the most dangerous situations for workers’ health. Surveillance systems based on occupational exposure registries contribute to support systematic improvement of working conditions.